MENGUJI KETEPATAN LAPORAN KEUANGAN PERUSAHAAN SEKTOR KESEHATAN DI INDONESIA: STRATEGI IMPLEMENTASI MODEL BENEISH M-SCORE DAN PENGARUHNYA DENGAN FRAUD PENTAGON - Ade Julianto Setya Putra; Helisa Noviarty; Juanda Astarani (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
Abstract This study investigates the influence of the fraud pentagon and the Beneish M-Score Model on the potential for financial statement fraud in healthcare companies listed on the Indonesia Stock Exchange (BEI). The fraud pentagon elements are represented by financial stability (pressure), ineffective monitoring (opportunity), auditor turnover (rationalization), board turnover (competence), and the number of CEO photos displayed in the annual report (arrogance). The study population encompasses all healthcare companies listed on the BEI from 2019 to 2023. A sample of 55 annual reports is employed for the analysis. Logistic regression is utilized as the statistical technique. The findings indicate that the examined variables do not exert a significant impact on financial statement fraud. This study serves as a foundation for future research to explore additional variables and expand the sample size to achieve more conclusive results. Keywords: Beneish M-Score; Fraud Pentagon; Financial Statement Fraud; Healthcare Companies